1998
DOI: 10.1074/jbc.273.33.21232
|View full text |Cite
|
Sign up to set email alerts
|

Role of N-Glycosylation in Human Angiotensinogen

Abstract: Human angiotensinogen, the specific substrate of renin, is a heterogeneous glycoprotein constitutively secreted by the liver. Different glycosylation levels may be responsible for its heterogeneity. It contains four putative asparagine-linked glycosylation sites (Asn-X-Ser/ Thr). Systematic site-directed mutagenesis (Asn replaced with Gln) of these four sites was undertaken, and 11 (single, double, triple, and quadruple (N-4)) mutants were produced in COS-7 and/or CHO-K1 cells and characterized. All of the sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…In vivo glycosylation has been shown to alter the stability, intracellular transport, secretion, distribution, and overall activity of a variety of proteins (Hilgenfeldt, 1988;Mann et al, 1996;Gimenez-Roqueplo et al, 1998;Barrios-De-Tomasi et al, 2002). We, along with others, have hypothesized that glycosylation of smaller peptides may have desirable effects on the pharmacokinetic and/or pharmacodynamic properties of the parent peptide (Albert et al, 1993;Polt et al, 1994;Negri et al, 1998;Susaki et al, 1999;Suzuki et al, 1999a,b;Bilsky et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo glycosylation has been shown to alter the stability, intracellular transport, secretion, distribution, and overall activity of a variety of proteins (Hilgenfeldt, 1988;Mann et al, 1996;Gimenez-Roqueplo et al, 1998;Barrios-De-Tomasi et al, 2002). We, along with others, have hypothesized that glycosylation of smaller peptides may have desirable effects on the pharmacokinetic and/or pharmacodynamic properties of the parent peptide (Albert et al, 1993;Polt et al, 1994;Negri et al, 1998;Susaki et al, 1999;Suzuki et al, 1999a,b;Bilsky et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although the P3 0 residue in human angiotensinogen is also His, whereas it is Tyr in pig and rat angiotensinogens, the role of His13 of human angiotensinogen is probably different from that of His13 of sheep angiotensinogen due to the N-glycosylation of adjacent Asn14. 25) We have reported that Tyr83 of human renin also contributes to biphasic pH dependence and that it is essential to the catalytic reaction at basic pH. 10) Tyr83 constitutes the S3 0 subsite pocket.…”
Section: )mentioning
confidence: 99%
“…Iodo (24) was analyzed by SDS-PAGE in non-reducing and reducing conditions (ϩdithiothreitol (DTT) 10 mM) after denaturation (4 min at 94°C). The gel was immediately stained using the colloidal blue stain kit (Novex).…”
Section: Methodsmentioning
confidence: 99%
“…The cells were transferred to serum-free medium (Dulbecco's modified Eagles's medium) 2 days after transfection and incubated for 48 h. The resulting supernatants containing recombinant proteins were analyzed on 9% SDS-PAGE with or without 2.5% ␤-mercaptoethanol and Western blotting (24). Angiotensinogen recombinants were detected with the anti-human angiotensinogen polyclonal antibody:HCL (diluted 1:6000) (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation